2018
DOI: 10.3389/fmicb.2018.02580
|View full text |Cite
|
Sign up to set email alerts
|

Puzzling Over the Pneumococcal Pangenome

Abstract: The Gram positive bacterium Streptococcus pneumoniae (pneumococcus) is a major human pathogen. It is a common colonizer of the human host, and in the nasopharynx, sinus, and middle ear it survives as a biofilm. This mode of growth is optimal for multi-strain colonization and genetic exchange. Over the last decades, the far-reaching use of antibiotics and the widespread implementation of pneumococcal multivalent conjugate vaccines have posed considerable selective pressure on pneumococci. This scenario provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 149 publications
(211 reference statements)
0
32
1
Order By: Relevance
“…The selection pressure of pneumococcal vaccine leads to dynamic changes in serotype distribution with subsequent emergence of NVTs (Hiller and Sa-Leao, 2018;Lo et al, 2019;Ouldali et al, 2019). Our surveillance data together with worldwide reports indicated the need of extending vaccine polyvalency.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The selection pressure of pneumococcal vaccine leads to dynamic changes in serotype distribution with subsequent emergence of NVTs (Hiller and Sa-Leao, 2018;Lo et al, 2019;Ouldali et al, 2019). Our surveillance data together with worldwide reports indicated the need of extending vaccine polyvalency.…”
Section: Discussionmentioning
confidence: 71%
“…Because changes in pneumococcal antimicrobial susceptibility and ongoing serotype replacement with emergence of new resistance lineages could occur under antibiotic and vaccine selective pressures (Hiller and Sa-Leao, 2018;Lo et al, 2019;Ouldali et al, 2019;Pinto et al, 2019), the World Health Organization (WHO) recommends that surveillance of pneumococcal infection should be continued for at least 5 years after implementation of PCV. The Taiwan Surveillance of Antimicrobial Resistance (TSAR) is a longitudinal multicenter surveillance program of clinical isolates to monitor the molecular epidemiology of bacterial pathogens and their trends of antimicrobial resistance (Huang et al, 2014;Wu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The pangenome analysis by Roary revealed a total of 1805 accessory genes found in 0% <= strains < 99% of the 80 strains analyzed. Those genes are mainly associated with evasion of the host immune system and virulence factors [21]. Nevertheless, our ndings showed that the accessory genomes in invasive sublineages were substantially smaller.…”
Section: Discussionmentioning
confidence: 70%
“…Contradictory findings on the role of phages in colonization and disease are perhaps not unforeseen given the wide genetic diversity of pneumococcal phages and the extraordinary plasticity of the pneumococcal genome, where the core genome constitutes merely a quarter of the pneumococcal pangenome [ 81 ]. It is thus likely that more factors than the simple presence of a phage, or a specific phage-encoded feature such as PblB, are at play.…”
Section: The Phage and The Host: Contribution To Virulence And Colmentioning
confidence: 99%